2021
DOI: 10.1002/adfm.202108650
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Nanoenzymes with Multifunctional Properties for Next‐Generation Biological and Environmental Applications

Abstract: As a powerful tool, nanoenzyme electrocatalyst broadens the ways to explore bioinspired solutions to the world's energy and environmental concerns. Efforts of fashioning novel nanoenzymes for effective electrode functionalization is generating innovative viable catalysts with high catalytic activity, low cost, high stability and versatility, and ease of production. High chemo‐selectivity and broad functional group tolerance of nanoenzyme with an intrinsic enzyme like activity make them an excellent environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 202 publications
0
30
0
Order By: Relevance
“…Bioinspired CNMs have been reported to have environmental and biomedical applications. 35 36 These catalysts have been incorporated as effective functionalized electrodes displaying high catalytic efficiency, cost-effectiveness, excellent stability, chemoselectivity, and ease of production. 35 Table 2 lists the various enzyme activities that can be mimicked by catalytic CNMs.…”
Section: Biomimetic Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinspired CNMs have been reported to have environmental and biomedical applications. 35 36 These catalysts have been incorporated as effective functionalized electrodes displaying high catalytic efficiency, cost-effectiveness, excellent stability, chemoselectivity, and ease of production. 35 Table 2 lists the various enzyme activities that can be mimicked by catalytic CNMs.…”
Section: Biomimetic Catalystsmentioning
confidence: 99%
“…35 36 These catalysts have been incorporated as effective functionalized electrodes displaying high catalytic efficiency, cost-effectiveness, excellent stability, chemoselectivity, and ease of production. 35 Table 2 lists the various enzyme activities that can be mimicked by catalytic CNMs. 36 However, the mechanisms involved in these biomimetic models are not completely understood due to lack of sufficient studies.…”
Section: Biomimetic Catalystsmentioning
confidence: 99%
“…However, due to the accumulation of active centers, their catalytic effect is often not as good as natural enzymes. 8 Since single-atom (SAs) materials were reported, more and more researchers have been attracted by the high atom utilization and extraordinary catalytic performance of SAs, 9,10 and they are committed to developing the unique value of SA materials in electrocatalysis. 11 Many studies have shown that the development of SA catalytic materials in electrochemical detection applications has obvious potential value.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a variety of nanomaterials with peroxidase activity for the electrochemical detection of H 2 O 2 have been developed. However, due to the accumulation of active centers, their catalytic effect is often not as good as natural enzymes . Since single-atom (SAs) materials were reported, more and more researchers have been attracted by the high atom utilization and extraordinary catalytic performance of SAs, , and they are committed to developing the unique value of SA materials in electrocatalysis .…”
Section: Introductionmentioning
confidence: 99%
“…Nanozymes are highly stable, efficient, and their synthesis is facile, compared with natural enzymes [1][2][3]. Research on nanozymes in the recent ten years showed them to be promising antibacterial nanomaterials to treat infectious diseases caused by pathogenic microorganisms [4,5]. Recently, nanomaterials with peroxidase-and oxidase-like activities have been intensively studied as two kinds of classical antibacterial agents [6,7].…”
Section: Introductionmentioning
confidence: 99%